Assessing conformations of small molecules with crystallographic databases. Issue 2 (9th March 2023) - McCabe, Patrick; Cole, Jason
Abstract : This work proposes a new way of assessing bond lengths, valence angles, torsion angles and molecular conformations using crystallographic distributions. Abstract : In this work, libraries of crystallographically determined bond lengths, valence angles and torsion angles derived from the Cambridge Structural Database (CSD) are used to generate a score to validate an individual bond length, valence angle or torsion angle. A single score can also be derived for each ensemble of bond lengths, ensemble of valence angles and ensemble of torsion angles in the molecule. The data used to compute the score for the individual parts of the molecule are also used to compute a single value assessing the specific conformation relative to the geometric molecular data contained in the CSD. Such a single‐number summary may be used, for example, to validate geometries of modelled molecules or molecular conformations in experimentally or computationally determined crystal structures. An example of how the score can be applied to an individual conformation is provided. Validation of the new score is performed by comparison with existing software for validating molecular geometries ( Mogul ) and a comparison with the CSD Conformer Generator scores is also carried out. Further application to the experimental standard deviation of C—C bonds of CSD entries is demonstrated, and the Platinum diverse data set is also studied.